Electron Paramagnetic Resonance of Nitrogenase and Nitrogenase Components from Clostridium pasteurianum W5 and Azotobacter vinelandii OP - Orme-Johnson, W. H. (1972)
The electron paramagnetic resonance of nitrogenase components, separately and together with the other reactants in the nitrogenase system (namely, reductant and Mg·ATP), have been examined at low temperatures (<20°K). The MoFe protein, component I or molybdoferredoxin, in the oxidized (but not oxygen-inactivated) state yields signals with g-values of 4.3, 3.7, and 2.01, and when reduced has no observable electron paramagnetic resonance. The Fe protein, component II, or azoferredoxin, yields a signal with g-values of 2.05, 1.94, and 1.89 in the reduced state that is converted by Mg·ATP into an axial signal with g-values near 2.05 and 1.94, and a second split signal near g = 4.3. The Fe protein has no definite electron paramagnetic resonance in the oxidized (not oxygen-denatured) state under these conditions. The Mg·ATP complex of reduced Fe protein reduces the MoFe protein, whereas dithionite alone does not reduce the MoFe protein. Reoxidation of the system by substrate leads to disappearance of the Fe protein signal and the reappearance of the MoFe protein signal. Thus Mg·ATP, which is hydrolyzed during substrate reduction, converts the Fe protein to a reductant capable of transferring electrons to MoFe protein, after which substrate reduction occurs.